The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-31291/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiome-Mediated Changes in Bone Metabolism Upon Infrared Light Exposure in Rats

Abstract: Background Adequate sunlight exposure helps reduce bone loss and is important to bone health. Currently, about 90% of the world population spends a major portion of daily life under artificial lighting. Unlike sunlight, LED white light, the main source of artificial lighting, has no infrared radiation, which is known to be beneficial to human health. In artificial lighting environments, infrared supplementation may be used to simulate the effects of sunlight on bone metabolism. Results Here, we supplemente… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…To clarify whether this effect is related to gut microbes. Lu et al (2021) supplemented white LED irradiation with infrared light in rats for three consecutive months and found that the abundance of Saccharibacteria and F/B ratio were significantly reduced, whereas the amounts of Clostridiaceae 1, Erysipelotrichaceae, Peptostreptococcaceae, Porphyromonadaceae, and Prevotellaceae were increased. This study suggested that infrared supplementation increased BMD and positively affected bone metabolism in rats by influencing the gut microbiota, reducing inflammation, and increasing butyrate production.…”
Section: Physical Factorsmentioning
confidence: 99%
“…To clarify whether this effect is related to gut microbes. Lu et al (2021) supplemented white LED irradiation with infrared light in rats for three consecutive months and found that the abundance of Saccharibacteria and F/B ratio were significantly reduced, whereas the amounts of Clostridiaceae 1, Erysipelotrichaceae, Peptostreptococcaceae, Porphyromonadaceae, and Prevotellaceae were increased. This study suggested that infrared supplementation increased BMD and positively affected bone metabolism in rats by influencing the gut microbiota, reducing inflammation, and increasing butyrate production.…”
Section: Physical Factorsmentioning
confidence: 99%